If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 7)(-7x + 4) = 0 Reorder the terms: (7 + 4x)(-7x + 4) = 0 Reorder the terms: (7 + 4x)(4 + -7x) = 0 Multiply (7 + 4x) * (4 + -7x) (7(4 + -7x) + 4x * (4 + -7x)) = 0 ((4 * 7 + -7x * 7) + 4x * (4 + -7x)) = 0 ((28 + -49x) + 4x * (4 + -7x)) = 0 (28 + -49x + (4 * 4x + -7x * 4x)) = 0 (28 + -49x + (16x + -28x2)) = 0 Combine like terms: -49x + 16x = -33x (28 + -33x + -28x2) = 0 Solving 28 + -33x + -28x2 = 0 Solving for variable 'x'. Factor a trinomial. (4 + -7x)(7 + 4x) = 0Subproblem 1
Set the factor '(4 + -7x)' equal to zero and attempt to solve: Simplifying 4 + -7x = 0 Solving 4 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -7x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -7x = 0 + -4 -7x = 0 + -4 Combine like terms: 0 + -4 = -4 -7x = -4 Divide each side by '-7'. x = 0.5714285714 Simplifying x = 0.5714285714Subproblem 2
Set the factor '(7 + 4x)' equal to zero and attempt to solve: Simplifying 7 + 4x = 0 Solving 7 + 4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 4x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 4x = 0 + -7 4x = 0 + -7 Combine like terms: 0 + -7 = -7 4x = -7 Divide each side by '4'. x = -1.75 Simplifying x = -1.75Solution
x = {0.5714285714, -1.75}
| -10x-4=11-7x | | -5x-4x+7=-5 | | 2x^4+18x^2+243=0 | | 5x+4x-8=1 | | 17+8-20=4(a-7)-3 | | 11-5= | | 4(2x-10)=-10(x-5) | | 3x+243=12x-9 | | 2x^4+18x^2-243=0 | | 218-2x=43x+23 | | Y=2x^2-16x+25 | | 17+2b-4c=4(a-7)-3 | | 192-6x=6x+12 | | y*12=-60 | | 7x+5-5x-2=11 | | 5a=0 | | 2x+2y+3z=3 | | 5y=13 | | -2x-5=x+7 | | -2w=-0,5 | | 4n^2-3n-13=0 | | 22(-c)=-66 | | 12-5x=2x^2 | | 33-16=8-16+5a+5 | | 12*5= | | (2x+1)(3x-8)=(5x-24)(2x-5)-192 | | 28-4a=6(2a-2)+24 | | 5x+1=2x+22 | | 0.80x-0.40(60+x)=-0.20(60) | | -5u-(-4)= | | x*2=7x | | 7(a-4)-2a=19+3(a+3) |